Celecoxib reduces cortical spreading depression–induced macrophage activation and dilatation of dural but not pial arteries in rodents: implications for mechanism of action in terminating migraine attacks. Issue 5 (May 2020) - Schain, Aaron J.; Melo-Carrillo, Agustin; Ashina, Sait; Strassman, Andrew M.; Burstein, Rami
Abstract : Abstract: Nonsteroidal anti-inflammatory drugs, commonly known as COX-1/COX-2 inhibitors, can be effective in treating mild to moderate migraine headache. However, neither the mechanism by which these drugs act in migraine is known, nor is the specific contribution of COX-1 vs COX-2. We sought to investigate these unknowns using celecoxib, which selectively inhibits the enzymatic activity of COX-2, by determining its effects on several migraine-associated vascular and inflammatory events. Using in vivo 2-photon microscopy, we determined intraperitoneal celecoxib effects on cortical spreading depression (CSD)-induced blood vessel responses, plasma protein extravasation, and immune cell activation in the dura and pia of mice and rats. Compared to vehicle (control group), celecoxib reduced CSD-induced dilatation of dural arteries and activation of dural and pial macrophages significantly, but not dilatation or constriction of pial arteries and veins, or the occurrence of plasma protein extravasation. Collectively, these findings suggest that a mechanism by which celecoxib-mediated COX-2 inhibition might ease the intensity of migraine headache and potentially terminate an attack is by attenuating dural macrophages' activation and arterial dilatation outside the blood–brain barrier, and pial macrophages' activation inside the blood–brain barrier. Abstract : Celecoxib mechanism of action in migraine termination involves attenuation of cortical spreading depression–induced dilatation of dural arteries and activation of dural and pial macrophages.